Stress as a risk factor of ischaemic heart disease among participants of the Programme of Preventive Measures in an Early Detection of Circulatory System Diseases - Maciak, Aleksandra; Bryła, Marek; Maniecka-Bryła, Irena (Polish Journal of Public Health, 2010)
Introduction. Stress was assessed as one of the independent risk factors for cardiovascular diseases. Many epidemiological data confirm the leading role of stress in developing the ischemic heart disease. In addition certain coronary heart disease risk factors, including smoking and high cholesterol level are associated with type A behavior, which has been acknowledged by Friedman and Rosenmann for the higher risk of having the ischemic heart disease and acute myocardial infarction. Aim. Aim of the research was to evaluate the prevalence of stress level amongst participants of Early Preventive cardiovascular Programme. Material and methods. The study was conducted from February till March 2008 amongst patients of a randomly chosen outpatient clinic. The tool f the research was a questionnaire survey, consisting of five diverse blocks with one concerning the stress perception. Diagnostic investigation, including blood cholesterol level, LDL and HDL fractions, triglyceride and glucose level, was taken. Double measurement of blood pressure was carried out. Former cardiovascular disease and/or diabetes was the criteria that disqualify from the participation in Early Preventive Programme. Collected data were statistically elaborated with Chi2 test. Results. High stress was found amongst 43.5% of participants. Women were more stressed than men. Stress influence the health self-assessment and particular health behavior. The place of work was the most stressful for all the participants. People who suffered from stress smoke cigarettes more frequently than relaxed ones. The correlation between stress and blood pressure and chosen parameters of lipids metabolism was verified. Conclusions. There is a strong need of implementation of cardiovascular preventive programme which include the socio-psychological factors in pathogenesis of cardiovascular diseases.